Difference between revisions of "2006 IMO Problems/Problem 4"
(→Solution) |
|||
Line 11: | Line 11: | ||
<cmath>2^x(1+2^{x+1}) = (2^{x+1}m + \varepsilon)^2 - 1 = 2^{2x-2}m^2 + 2^xm\varepsilon,</cmath> | <cmath>2^x(1+2^{x+1}) = (2^{x+1}m + \varepsilon)^2 - 1 = 2^{2x-2}m^2 + 2^xm\varepsilon,</cmath> | ||
or, equivalently <cmath>1 + 2^{x+1} = 2^{x-2}m^2 + m\varepsilon.</cmath> Therefore <cmath>1 - \varepsilon m = 2^{x-2}(m^2 - 8).\qquad(\dagger) </cmath> For <math>\varepsilon = 1</math> this yields <math>m^2 - 8 < 0</math>, i.e. <math>m=1</math>, which fails to satisfy <math>(\dagger)</math>. For <math>\varepsilon = -1</math> equation <math>(\dagger)</math> gives us <cmath>1 + m = 2^{x-2}(m^2 - 8) \geq 2(m^2 - 8),</cmath> implying <math>2m^2 - m - 17 \leq 0</math>. Hence <math>m\leq 3</math>; on the other hand <math>m</math> cannot be <math>1</math> by <math>(\dagger)</math>. Because <math>m</math> is odd, we obtain <math>m=3</math>, leading to <math>x=4</math>. From <math>(*)</math> we get <math>y=23</math>. These values indeed satisfy the given equation. Recall that then <math>y = -23</math> is also good. Thus we have the complete list of solutions <math>(x,y)</math>: <math>(0,2)</math>, <math>(0,-2)</math>, <math>(4,23)</math>, <math>(4,-23)</math>. | or, equivalently <cmath>1 + 2^{x+1} = 2^{x-2}m^2 + m\varepsilon.</cmath> Therefore <cmath>1 - \varepsilon m = 2^{x-2}(m^2 - 8).\qquad(\dagger) </cmath> For <math>\varepsilon = 1</math> this yields <math>m^2 - 8 < 0</math>, i.e. <math>m=1</math>, which fails to satisfy <math>(\dagger)</math>. For <math>\varepsilon = -1</math> equation <math>(\dagger)</math> gives us <cmath>1 + m = 2^{x-2}(m^2 - 8) \geq 2(m^2 - 8),</cmath> implying <math>2m^2 - m - 17 \leq 0</math>. Hence <math>m\leq 3</math>; on the other hand <math>m</math> cannot be <math>1</math> by <math>(\dagger)</math>. Because <math>m</math> is odd, we obtain <math>m=3</math>, leading to <math>x=4</math>. From <math>(*)</math> we get <math>y=23</math>. These values indeed satisfy the given equation. Recall that then <math>y = -23</math> is also good. Thus we have the complete list of solutions <math>(x,y)</math>: <math>(0,2)</math>, <math>(0,-2)</math>, <math>(4,23)</math>, <math>(4,-23)</math>. | ||
+ | |||
+ | ==See Also== | ||
+ | |||
+ | {{IMO box|year=2006|num-b=3|num-a=5}} |
Latest revision as of 00:03, 19 November 2023
Problem
Determine all pairs of integers such that
Solution
If is a solution then obviously
and
is a solution too. For
we get the two solutions
and
.
Now let be a solution with
; without loss of generality confine attention to
. The equation rewritten as
shows that the factors
and
are even, exactly one of them divisible by
. Hence
and one of these factors is divisible by
but not by
. So
Plugging this into the original equation we obtain
or, equivalently
Therefore
For
this yields
, i.e.
, which fails to satisfy
. For
equation
gives us
implying
. Hence
; on the other hand
cannot be
by
. Because
is odd, we obtain
, leading to
. From
we get
. These values indeed satisfy the given equation. Recall that then
is also good. Thus we have the complete list of solutions
:
,
,
,
.
See Also
2006 IMO (Problems) • Resources | ||
Preceded by Problem 3 |
1 • 2 • 3 • 4 • 5 • 6 | Followed by Problem 5 |
All IMO Problems and Solutions |